The Gender Dichotomy in Pakistani Social Context - Fatima Safdar,; Dr. Shahzadi Pakeeza,; Fariha Fatima, (Al-Qanṭara, 2024)
This article introduces Gender Dichotomy in Pakistani context and Pakistani constitutions regarding family laws. This chapter will provide a historical perspective on Gender discrimination in Pakistan. Although it is significantly forbidden, gender discrimination has historically been one of Pakistan's biggest challenges. Gender discrimination is still deeply rooted in Pakistan. Though the Pakistani Constitution guarantees women's rights, it's crucial to observe how state legislation and other establishments carry out these legal protections for women. Because of the patriarchal society and socially constructed customs, gender violence against women in Pakistan caused numerous issues for the women. The advancement of rights for women and female empowerment is a major focus of Pakistani society. This chapter analyzed how family laws empowered women. However, it is essential that the state and its institutions address these laws and guarantee that they are applied fairly. Furthermore, the issue of gender discrimination needs to be securitized by the government of Pakistan as an issue of strategy. Additionally, create committees to address concerns based on gender and provide each gender equal rights. Keywords- Gender Dichotomy in Pakistani Social Context